ASSET FORFEITURE AS A LAW ENFORCEMENT TOOL. (14th April 2015) - Miceli, Thomas J.; Johnson, Derek
Abstract : This article examines the impact on deterrence of laws that allow the seizure of assets used in the commission of a crime but owned by someone other than the offender. The results suggest that forfeiture can be used effectively, in combination with more standard tools (criminal fines or imprisonment), as a deterrent under certain conditions, but the risk of overuse is real. In particular, complete forfeiture (seizure of the entire value of the asset) is not generally socially optimal, but when enforcers are rent‐seekers who care primarily about the revenue generated by forfeiture, they will use the tool to the maximum extent allowed by law. ( JEL H11, K14, K41)